Performance of Hand Movements by 3–5-Year-Old Girls with Different Handedness - Galamanzhuk, L; Smolianko, Y; Hudyma, N; Balatska, L; Mytskan, T; Mysiv, V; Marchuk, V (Physical Education Theory and Methodology, 2022)
Abstract The purpose of the study was to determine the state of performance of motor actions by girls with different handedness, which establishes a valid program for each age period of 3–5 years. Materials and methods. Sixty girls took part in the study (compared with the right-, left-hand preference, and ambidexterity), each attended a preschool, and at the time of the study, the age of each was within the range of 3 years 5 months 2 days to 3 years 5 months and 29 days. To obtain the necessary data, motor actions determined by the current child development program in the preschool period were used. The quality of the girls' performance of each defined motor action was assessed, and the procedure took place in January of each new school year, that is, when the girls were first 3 years old, then 4 and 5 years old. Results. Each age of the period of 3–5 years is marked by handedness-related features of development and manifestation of the motor function of girls when performing motor actions with their hands. At the same time, the majority of motor actions were performed by the girls of each sample with a score lower than the maximum score. This does not contribute to the intensive development of the motor function of girls, which differs from the task defined by the current program for preschool education institutions. Comparing the results of girls with different handedness, it was found that in most motor actions, the scores obtained for performance differ by a statistically significant amount, and at each age of the studied period. Conclusions. Establishing features in the quality of performance of motor actions by girls with different handedness at each age period of 3–5 years is an important task. To increase the effectiveness of the educational process, the teacher needs to pay more attention to the study of those motor actions that were evaluated with low scores in girls with a certain preferred hand.
Keywords: дівчата, дошкільний вік, асиметрія рук, рухова функція, розвиток